Psychometric properties of the Child Problematic Traits Inventory in Portuguese children - Barroso, Ricardo (2024)
Abstract: The Child Problematic Traits Inventory (CPTI) is a teacher-reported instrument to assess psychopathic personality traits in 3 to 6-year-old children (M=4.78, SD=.60). This is the first study to test the reliability and validity of this instrument within a Portuguese sample of 264 children aged between 3 to 6 years (43.2% female). Cronbach alpha values greater than .80 were observed for all CPTI scale scores. Regarding the criterion validity, CPTI total and its three dimensions were significantly correlated with an alternative measure of impulsiveness. The CPTI items loaded differently on the three theoretically proposed factors: (1) Interpersonal/Grandiose-Deceitful, (2) Affective/Callous-Unemotional, and (3) Behavioral/Impulsive-Need for Stimulation. The Total CPTI and the three dimensions of CPTI were significantly correlated with the alternative measure of Impulsiveness – CBQ Impulsivity subscale (r=.37Total; .29Interpersonal; .26Affective; .45Behavioral). In conclusion, our findings suggest that the CPTI is a psychometrically sound measure to assess psychopathic personality traits in a sample of community-residing Portuguese children.